P-253 The Collaborative Cross as a Resource to Study Gene-environment Interactions Involved in IBD. (February 2017) - Rogala, Allison; Godfrey, Virginia
Abstract : Background: The pathogenesis of inflammatory bowel disease (IBD) is considered to be the result of a convergence of a dysregulated immune response to environmental factors in a genetically susceptible host. Human genome wide association studies (GWAS) have identified over 200 different loci contributing to IBD susceptibility, highlighting the tremendous genetic complexity and underlining the need for better understanding of their functional role in IBD pathogenesis such that better treatments may be developed. Mouse models of IBD are typically created through genetic manipulation or chemical induction of colitis; however, few spontaneous murine models of colitis exist. Recently, a panel of recombinant inbred mouse strains, the Collaborative Cross (CC), has been developed to map complex genetic diseases such as IBD. Unlike standard recombinant inbred lines, the CC lines include greater genetic variation through the inclusion of 5 standard and 3 wild-derived founders. The recombination of alleles from these 8 diverse founders led to the development of lines with atypical phenotypes including a line, CC011/Unc, which exhibits spontaneous colitis in the absence of known murine pathogens, Helicobacter species, or murine Norovirus. We have previously identified 4 genetic loci contributing to the colitis phenotype, 3 of which have not been previously associated with murine models of colitis. Given the desire to utilize this model to interrogate the interactions between host genetics and environmental factors such as the intestinal microbiota, we sought to determine if the environment affects the colitis phenotype of CC011/Unc. Methods: To answer this question, CC011/Unc mice were rederived into recipient dams colonized with defined Altered Schaedler Flora (ASF) and maintained alongside the original CC011/Unc (denoted as specific pathogen free or SPF) colony in the same facility under otherwise identical housing conditions. Colons of aged mice (22–65 weeks, mean = 42 weeks) were scored for degree of histologic colitis (max score = 18). Results: CC011/Unc mice colonized with ASF flora exhibited significantly lower histologic colitis scores (mean = 0.28, n = 50) as compared to SPF mice (mean = 6.32, n = 41). We next asked whether the colitis phenotype is transmissible by cohousing 15 ASF weanlings with SPF CC011/Unc mice for a duration of 20 weeks. Whereas all SPF mice survived, only 10 of the original 15 ASF survived for the entire length of the study. Upon necropsy of the surviving mice, formerly ASF mice exhibited marked splenomegaly ( P < 0.01) as compared to SPF mice. Additionally, all formerly ASF mice exhibited gross colonic thickening. Conclusions: Based upon these experiments, we conclude the colitis phenotype exhibited by the CC011/Unc mouse strain is dependent on environmental factors, which are transmissible via cohousing. Coupled with the complex genetic loci responsible for the spontaneous colitis exhibited by the CC011/Unc strain, these findings further support the value of this murine model in the study of mechanisms of host-gene-environment interactions involved in the pathogenesis of IBD. Future studies will seek to identify the specific environmental factors and pathways influencing the phenotype and utilize additional CC strains containing different combinations of these loci to further interrogate these genetic interactions.